Entrepreneurial Marketing, Corporate Reputation, Corporate Creativity and Competitive Advantage: A Research Framework and Proposition - Gontur, Silas; Jonathan Vem, Linus; Goyit, Meshach Gomam; Davireng, Macrop (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
This study explored the consequences of entrepreneurial marketing by creating empirical evidence grounded in dynamic capability view and image theory. The study proposed a direct and indirect relationship between entrepreneurial marketing and competitive advantage, recognizing corporate creativity as the boundary condition on the entrepreneurial marketing-competitive advantage link suggesting a moderated entrepreneurial marketing model. The study explained the theoretical and practical contribution of the study in our understanding of entrepreneurial marketing practices and the role of corporate reputation. Corporate creativity was also discussed especially from the perspective of entrepreneurial firms.